Pengaruh kepribadian hardiness dan kepemimpinan transformational terhadap kinerja karyawan PDAM Kota Malang - Muslimin Muslimin (Fakultas Psikologi, 2020)
Employee performance is influenced by several factors such as internal factors and external factors. The purpose of this study was to determine the effect of hardiness and transformational leadership on employee performance simultaneously or together. The sampling technique uses simple random sampling in one of the PDAM companies in Malang. Subjects in this study were 150 employees. The data collection method in this study uses a hardiness personality scale, transformational leadership scale and employee performance scale. The results of the analysis of the multiple regression test showed that the hardiness and transformational leadership influences simultaneously or jointly on employee performance with an influence contribution of 49%. While partially transformational leadership has no influence on employee performance.